Synthesis and Characterization of the Complexes of Cobalt(II), Nickel(II), Copper(II) and Zinc(II) with 2-(2-carboxyphenylazo)-1,3-diketones - CHERIYAN, MATHEWS; MOHANAN, K. (Asian Journal of Chemistry, 2010)
Cobalt(II), nickel(II), copper(II) and zinc(II) complexes with three potentially tridentate ligands formed by coupling of diazotised anthranilic acid with 1,3-diketones (acetylacetone, benzoylacetone, dibenzoylmethane) have been synthesized and characterized on the basis of elemental analysis, molar conductance, magnetic susceptibility, UV-Visible, IR and NMR spectral data. The spectral studies reveal that the ligands exist in the hydrazone form rather than the azo-enol form and coordinated to the metal ion through one of the carbonyl groups of the 1,3-diketone moiety, carboxylate oxygen and deprotonated hydrazeno nitrogen. All the complexes exhibit 1:1 metal ligand ratio. On the basis of UV-Visible spectral data and magnetic susceptibility, suitable geometry has been proposed for each metal complex. The EPR spectral data reveal that the metal-ligand bond has considerable covalent character. The copper(II) complexes have been screened for their antibacterial properties. It has been observed that the metal complexes are more potent bactericides than the ligands.